The Korean Organ Transplantation Registry (KOTRY): an overview and summary of the kidney-transplant cohort - Hee Jung Jeon; Tai Yeon Koo; Man Ki Ju; Dong-Wan Chae; Soo Jin Na Choi; Myoung Soo Kim; Jung-Hwa Ryu; Jong Cheol Jeon; Curie Ahn; Jaeseok Yang (The Korean Society of Nephrology, 2022)
Background As the need for a nationwide organ-transplant registry emerged, a prospective registry, the Korean Organ Transplantation Registry (KOTRY), was initiated in 2014. Here, we present baseline characteristics and outcomes of the kidney-transplant cohort for 2014 through 2019. Methods The KOTRY consists of five organ-transplant cohorts (kidney, liver, lung, heart, and pancreas). Data and samples were prospectively collected from transplant recipients and donors at baseline and follow-up visits; and epidemiological trends, allograft outcomes, and patient outcomes, such as posttransplant complications, comorbidities, and mortality, were analyzed. Results From 2014 to 2019, there were a total of 6,129 registered kidney transplants (64.8% with living donors and 35.2% with deceased donors) with a mean recipient age of 49.4 ± 11.5 years, and 59.7% were male. ABO-incompatible transplants totaled 17.4% of all transplants, and 15.0% of transplants were preemptive. The overall 1- and 5-year patient survival rates were 98.4% and 95.8%, respectively, and the 1- and 5-year graft survival rates were 97.1% and 90.5%, respectively. During a mean follow-up of 3.8 years, biopsy-proven acute rejection episodes occurred in 17.0% of cases. The mean age of donors was 47.3 ± 12.9 years, and 52.6% were male. Among living donors, the largest category of donors was spouses, while, among deceased donors, 31.2% were expanded-criteria donors. The mean serum creatinine concentrations of living donors were 0.78 ± 0.62 mg/dL and 1.09 ± 0.24 mg/dL at baseline and 1 year after kidney transplantation, respectively. Conclusion The KOTRY, a systematic Korean transplant cohort, can serve as a valuable epidemiological database of Korean kidney transplants.